"Type C appendicular duplication with patent vitello-intestinal duct-an unforeseen association"-a case report - S. Rajkiran Raju; A. R. Prasanna Kumar; A. M. Shubha; Julian Crasta (SpringerOpen, 2021)
Abstract Background Gastrointestinal duplications are uncommon occurring in 1 in 5000 live births. Small intestine is commonly involved, while appendicular duplications are extremely rare. Vitelline duct anomalies arise due to failure of involution of the omphalomesenteric duct. Their spectrum ranges from a simple umbilical sinus to completely patent omphalomesenteric fistulae. We report here a rare association of complete appendico-cecal duplication with patent vitello-intestinal duct (PVID). Case presentation A 14-year-old girl who presented with complaints of scant, foul smelling, and feculent discharge from umbilicus intermittently since birth was evaluated and diagnosed to have a patent vitello-intestinal duct. At laparotomy, a patent vitello-intestinal tract opening unusually at the ileo-cecal junction was noted. In addition, an appendico-cecal duplication cyst bearing an appendix on the mesenteric side and a 4-cm long orthotopic appendix on the native cecum was found with the duplex cecum sharing a common wall and blood supply. The terminal ileum with the duplication and patent vitello-intestinal duct were excised in toto, and an end-to-end ileo-ascending anastomosis was done. The child is well at 1 year follow-up. Conclusion A complete appendico-cecal (Type C) duplication with ectopically inserted patent vitello-intestinal duct is reported here as an unusual association, discussing its management and the probable disarray in the embryological development.